Pharmacological properties, molecular mechanisms and therapeutic potential of ginsenoside Rg3 as an antioxidant and anti-inflammatory agent - Wang, Jing; Zeng, Li; Zhang, Ying; Qi, Wenxiu; Wang, Ziyuan; Tian, Lin; Zhao, Daqing; Wu, Qibiao; Li, Xiangyan; Wang, Tan (Frontiers in Pharmacology, 2022)
Inflammation and oxidative stress lead to various acute or chronic diseases, including pneumonia, liver and kidney injury, cardiovascular and cerebrovascular diseases, metabolic diseases, and cancer. Ginseng is a well-known and widely used ethnic medicine in Asian countries, and ginsenoside Rg3 is a saponin isolated from Panax ginseng C. A. Meyer, Panax notoginseng, or Panax quinquefolius L. This compound has a wide range of pharmacological properties, including antioxidant and anti-inflammatory activities, which have been evaluated in disease models of inflammation and oxidative stress. Rg3 can attenuate lung inflammation, prevent liver and kidney function damage, mitigate neuroinflammation, prevent cerebral and myocardial ischemia–reperfusion injury, and improve hypertension and diabetes symptoms. The multitarget, multipathway mechanisms of action of Rg3 have been gradually deciphered. This review summarizes the existing knowledge on the anti-inflammatory and antioxidant effects and underlying molecular mechanisms of ginsenoside Rg3, suggesting that ginsenoside Rg3 may be a promising candidate drug for the treatment of diseases with inflammatory and oxidative stress conditions.